2001
DOI: 10.1038/sj.bdj.4800944
|View full text |Cite
|
Sign up to set email alerts
|

Can dental attendance improve quality of life?

Abstract: A random probability sample of 3,000 addresses was selected in a multistage sampling technique. One hundred postal sectors were selected and within each sector 30 addresses were selected randomly. Of the 3,000 selected addresses 2,668 were eligible addresses. Ineligible addresses included new and empty premises at which no private households were dwelling. Trained interviewers sought to carry out face-to-face interviews with an adult respondent (aged 16 or older) at eligible addresses. Only one adult household… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 10 publications
4
59
0
2
Order By: Relevance
“…Studies have demonstrated association between dental attendance and the perception of an enhanced quality of life. [21][22][23] Also of interest is the better periodontal health in the US when measured by periodontal pocket depth and clinical attachment loss. One explanation could be the accuracy of the measure.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated association between dental attendance and the perception of an enhanced quality of life. [21][22][23] Also of interest is the better periodontal health in the US when measured by periodontal pocket depth and clinical attachment loss. One explanation could be the accuracy of the measure.…”
Section: Discussionmentioning
confidence: 99%
“…(24) found that when dental attendance was problem- motivated it was associated with higher levels of social impact, and a poorer OHQoL. McGrath & Bedi (5) performed an epidemiological study on British Adults and found that those reporting a dental visit within the previous year felt that oral health enhanced their quality of life, after controlling for socio-demographic confounders. Recently a prospective cohort study performed on adolescents and young adults in New Zealand has shown that the long-term routine dental attendance is clearly associated with a better oral health status, as assessed both clinically and subjectively (4).…”
Section: Discussionmentioning
confidence: 99%
“…For OHQoL assessment, a large variety of instruments (questionnaire and scales) has been developed over the past three decades (11), generally being applied as descriptive measures in cross-sectional studies. Recent epidemiological studies have found that problem-oriented attendees have a poorer dental status and a lower oral-health-related quality of life (5,12-14). …”
Section: Introductionmentioning
confidence: 99%
“…All of these factors contribute negatively to the oral health-related quality of life in the elderly. The professional dental care can significantly enhance the quality of life for patients by effectively diagnosing and managing the conditions [18,19]. Hence, the prevalence studies are important to report the frequency of HS among the particular population.…”
Section: Introductionmentioning
confidence: 99%